Desconstruindo a promessa desenvolvimentista: horizonte pós-neoextrativista para a América Latina a partir de Ecossocialismo e Ecofeminismo - Montaño, Maiara Michele Beckrich (2024)
Abstract: The research aims to demonstrate how the development-extractive paradigm was consolidated as a way of inserting Latin America into the global economy and to debate forms of resistance to this model which, instead of the abundance promised by the North, produced massive impoverishment and intense environmental degradation. To unveil the intrinsic relationship between development and coloniality, I take the Modernity/Coloniality group as the greatest theoretical reference, which, in addition to presenting this historical process, proposes the denaturalization of the concept of development so that we can analyze it in a truly critical manner. In the second part of the research, I debate alternatives for the region, focusing on Ecosocialism and Ecofeminism, counter-hegemonic streams that have been articulated in Latin America to propose ways of life that question this logic of exploitation. Finally, in addition to outlining some of the relevant divergences between the ways in which Ecofeminism and Ecosocialism have interacted historically, I discuss their similarities, especially with regard to the centrality given to Political Ecology and the mobilization of values and practices of those marginalized by the system in their transformation proposals. As a general methodology, I depart from a critical perspective on the capitalist macrostructure based on Marxism, aiming to also open space for a post-structuralist vision that considers the multiplicity and specificity of manifestations of the power of Capital within the Latin American population, especially with regard to aspects of race and gender